Preparation method of lithium manganese iron phosphate material based on secondary sintering process

Through the preparation method based on the di-sintering process, uniform mixing of iron-manganese elements in the lithium manganese phosphate positive electrode material is achieved, solving the problem of poor material circulation performance and improving conductivity and charge and discharge efficiency.

CN119419240APending Publication Date: 2025-02-11HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411530213.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform mixing of iron-manganese elements in lithium manganese phosphate positive electrode materials, resulting in poor circulation performance of the material.

Method used

Using the preparation method based on the di-sintering process, firstly the magnesium ion-doped lithium iron phosphate and carbon-coated manganese dioxide are ball milled, then mixed with the phosphoric acid solution and sand-milled and calcined, and finally secondary calcination is performed to obtain iron manganese phosphate. Lithium material.

Benefits of technology

By uniformly mixing iron and manganese elements, the conductivity and charge and discharge efficiency of the material are improved, and the cycling performance and capacitance of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419240A_ABST
    Figure CN119419240A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium manganese iron phosphate material based on a secondary sintering process, and belongs to the technical field of lithium battery manufacturing. The method comprises the following steps: S1, carrying out ball milling treatment on magnesium ion-doped lithium iron phosphate and carbon-coated manganese dioxide to obtain a mixed material; s2, mixing and sanding the obtained mixed material and a phosphoric acid solution, drying, and calcining under the protection of inert gas to obtain a magnesium ion doped lithium manganese iron phosphate material; and S3, mixing the magnesium ion doped lithium manganese iron phosphate material, lithium nitrate and glucose, sanding, drying, and carrying out secondary calcination to obtain the lithium manganese iron phosphate material. Manganese dioxide is subjected to carbon wrapping, and the diffusion coefficient of Mn < 4 + > is increased through a formed protective film; carbon in the MnO2 composite material forms a carbon layer with good conductivity on the surface of MnO2, and the carbon layer protects the internal active material from being dissolved by electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery manufacturing, and in particular relates to a method for preparing lithium manganese iron phosphate material based on a di-sintering process. Background Art

[0002] There are many types of positive electrode materials for lithium-ion batteries, the main varieties are lithium cobalt oxide, lithium manganese oxide, nickel-manganese-cobalt ternary materials and lithium iron phosphate. Among them, lithium iron phosphate has a relatively regular olivine structure, which makes lithium iron phosphate have the advantages of large discharge capacity, low price, non-toxicity and low pollution to the environment. However, due to its structural limitations, lithium iron phosphate has the disadvantages of low electronic conductivity, small lithium ion diffusion coefficient and low material tap density, which greatly limits the application of lithium iron phosphate. In order to broaden the application of lithium iron phosphate, manganese compounds are currently introduced into lithium iron phosphate to form lithium iron manganese phosphate solid solution. Since manganese compounds have higher electrochemical reaction voltage and better electrolyte compatibility, lithium iron manganese phosphate solid solution obtains better capacity and cycle effect.

[0003] Existing synthetic LiMn x Fe 1-x The methods for PO4 solid solution materials generally include high temperature solid phase reaction method, liquid phase coprecipitation method, hydrothermal method, sol-gel method, redox method, solid phase microwave method and mechanical ball milling method, etc. At present, the commonly used ones are high temperature solid phase reaction method and hydrothermal method.

[0004] The patent with publication number CN102769131 A discloses a method for preparing lithium iron manganese phosphate / carbon composite material, which uses ammonium dihydrogen phosphate, lithium source, manganese source, iron source, carbon source and metal doping elements as raw materials, mixes and dries, heats to 450-700°C under atmospheric conditions and dries at a constant temperature for 1-12 hours, and then cools to obtain lithium iron manganese phosphate / carbon composite material. This method has the following disadvantages: 1. It is difficult to evenly coat the carbon source on the surface of the positive electrode material by solid phase method; 2. Since there are two transition metal elements, manganese and iron, in the process of preparing the material, it is necessary to fully consider how to evenly mix the two elements. If even mixing is not achieved, the electrochemical performance of the prepared material cannot meet the requirements of commercial application, and the solid phase method used in this patent cannot achieve the purpose of evenly mixing the two elements.

[0005] Therefore, it is necessary to find a method for uniformly mixing iron and manganese to prepare a lithium iron manganese phosphate positive electrode material with high capacity and high cycle performance. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a lithium iron manganese phosphate material based on a di-sintering process to solve the problem of poor cycle performance of the lithium iron manganese phosphate positive electrode material.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing lithium iron manganese phosphate material based on a di-sintering process comprises the following steps:

[0009] S1. Ball milling the magnesium ion-doped lithium iron phosphate and the carbon-coated manganese dioxide to obtain a mixed material;

[0010] S2, mixing the obtained mixed material with the phosphoric acid solution, sand-milling, drying, and calcining under the protection of an inert gas to obtain a magnesium ion-doped lithium manganese iron hydrogen phosphate material;

[0011] S3, mixing the magnesium ion-doped lithium manganese iron phosphate material, lithium nitrate and a carbon source, sand-milling, drying, and secondary calcining to obtain the lithium manganese iron phosphate material.

[0012] Furthermore, the molar ratio of the magnesium ion-doped lithium iron phosphate to the carbon-coated manganese dioxide is 1.1-1.2:0.7-0.8.

[0013] Furthermore, the mass ratio of the mixed material to the phosphoric acid solution is 1:6-8; and the concentration of the phosphoric acid solution is 1 mol / L.

[0014] Furthermore, the carbon source is one of glucose and PEG400; the mass ratio of the magnesium ion-doped lithium manganese iron phosphate material, lithium nitrate and carbon source is 9-10:1-1.5:1-1.5.

[0015] Furthermore, the magnesium ion-doped lithium iron phosphate is prepared by the following method:

[0016] PEG400, 1 mol / L H3PO4 solution and 1 mol / L LiOH solution were stirred evenly, and when the pH value was adjusted to be stable at 11.5-12.0, 0.5 mol / L MgSO4 solution and 0.5 mol / LFeSO4 solution were added, stirred for 5-10 min, reacted at 180°C for 12-14 h, washed, and dried to obtain magnesium ion-doped lithium iron phosphate.

[0017] Furthermore, the usage ratio of the PEG400, H3PO4 solution, LiOH solution, MgSO4 solution and FeSO4 solution is 130-140 mL: 35-40 mL: 105-110 mL: 3-4 mL: 40-45 mL.

[0018] Furthermore, the carbon-coated manganese dioxide is prepared by the following method:

[0019] Add KMnO4 and MnSO4·H2O to deionized water respectively, and ultrasonically heat to 90°C until all the reagents are dissolved to obtain KMnO4 solution and MnSO4 solution; slowly and uniformly pour the KMnO4 solution into the MnSO4 solution while stirring continuously, and react at 55-60°C for 1-2h; vacuum filter, wash, dry, and grind to obtain manganese dioxide powder;

[0020] Manganese dioxide powder and a carbon source are added to deionized water, stirred for 0.5 to 1 hour, heated to 150 to 160° C., cooled to room temperature, washed, vacuum dried at 75 to 80° C. for 12 to 14 hours, and fully ground to obtain carbon-coated manganese dioxide.

[0021] Furthermore, the usage ratio of KMnO4, MnSO4·H2O and deionized water is 1.6-1.8 g: 2.6-2.9 g: 50-60 mL.

[0022] Furthermore, the carbon source is one of glucose and PEG400; the dosage ratio of the manganese dioxide powder, the carbon source and the deionized water is 15 mg: 20-40 mg: 20-30 mL.

[0023] For pure MnO2, the electrolyte first contacts the surface of the active material. 4+ Transformed into Mn 3+ , Mn 3+ The structure formed by adding an appropriate amount of glucose can improve the electrochemical performance of MnO2, because the particles of carbon-coated active materials are evenly distributed, and carbon forms a protective film on the surface of MnO2 particles, which inhibits the growth of grains, reduces the size of particles, and shortens the MnO2. 4+ The deintercalation pathway in solution increases the Mn 4+ The diffusion coefficient.

[0024] However, too much carbon content will destroy the shell structure and form an irregular block structure. At the same time, a large amount of amorphous carbon coated on the surface of MnO2 hinders the growth of manganese dioxide to each crystal plane, making the MnO2 crystal amorphous, and it is difficult for the electrolyte to contact the active material, which seriously affects the performance of MnO2.

[0025] Beneficial effects of the present invention:

[0026] (1) The present invention provides a lithium manganese iron phosphate material based on a sintering process, in which a manganese source is first synthesized into manganese dioxide and then mixed with lithium iron phosphate. The pores formed between the manganese dioxide particles ensure that the electrolyte and the active material are in full contact, thereby improving the conductivity and charge and discharge efficiency of the material; the manganese dioxide is then carbon-wrapped, and the carbon forms a protective film on the surface of the MnO2 particles, which inhibits the growth of the grains, reduces the particle size, and shortens the Mn 4+ The deintercalation pathway in solution increases the Mn 4+ Secondly, the carbon in the MnO2 composite material forms a carbon layer with good conductivity on the surface of MnO2. The carbon layer protects the active material inside from being dissolved by the electrolyte and ensures that the structure of the active material is not destroyed.

[0027] (2) The magnesium ion-doped lithium iron phosphate used in the present invention, wherein Mg 2+ There is no electrochemical activity, and no redox reaction occurs during the charge and discharge process, which can reduce the phase change of the material during the charge and discharge process, reduce the lattice volume change, and improve the interface stability of the material; in addition, Mg 2+ Doping can reduce the length of the Mn-O bond and increase the length of the Li-O bond, thereby increasing the Li+ transmission channel and making manganese dioxide more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described below in conjunction with the accompanying drawings.

[0029] Figure 1 Schematic diagram of 0.1C charge-discharge curves of lithium manganese iron phosphate materials prepared in various embodiments and comparative examples of the present invention;

[0030] Figure 2 This is a SEM image of the lithium manganese iron phosphate material prepared in Example 1 of the present invention;

[0031] Figure 3 is a SEM image of the lithium manganese iron phosphate material prepared in Example 7 of the present invention;

[0032] Figure 4 This is a SEM image of the lithium manganese iron phosphate material prepared in Comparative Example 4 of the present invention; DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] This embodiment provides a method for preparing lithium manganese iron phosphate material based on a di-sintering process, which is prepared by the following steps:

[0036] S1. Stir 130 mL PEG400, 35 mL 1 mol / L H3PO4 solution and 105 mL 1 mol / L LiOH solution, adjust the pH value to stabilize at 12.0, add 3 mL 0.5 mol / LMgSO4 solution and 40 mL 0.5 mol / LFeSO4 solution, stir for 5 min, react at 180 ° C for 12 h, wash, and dry to obtain magnesium ion-doped lithium iron phosphate;

[0037] 1.6 g KMnO4 and 2.6 g MnSO4·H2O were added to 50 mL deionized water, and ultrasonically heated to 90°C until all the reagents were dissolved to obtain KMnO4 solution and MnSO4 solution; the KMnO4 solution was slowly and uniformly poured into the MnSO4 solution with continuous stirring, and reacted at 60°C for 1 h; vacuum filtered, washed, dried, and ground to obtain manganese dioxide powder; then 15 mg manganese dioxide powder and 30 mg glucose were added to 20 mL deionized water, stirred for 0.5 h, heated to 160°C, cooled to room temperature, washed, vacuum dried at 80°C for 12 h, and fully ground to obtain carbon-coated manganese dioxide.

[0038] Ball milling magnesium ion-doped lithium iron phosphate and carbon-coated manganese dioxide in a molar ratio of 1.2:0.7 to obtain a mixed material;

[0039] S2, mixing 10 g of the mixed material with 60 mL of 1 mol / L phosphoric acid solution, grinding, drying, and calcining under inert gas protection to obtain a magnesium ion-doped lithium manganese iron hydrogen phosphate material;

[0040] S3. 9 g of magnesium ion-doped lithium manganese iron phosphate material, 1.5 g of lithium nitrate and 1.5 g of glucose are mixed, sand-milled, dried, and calcined twice to obtain the lithium manganese iron phosphate material.

[0041] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 As shown; the SEM image of lithium manganese iron phosphate material is as follows Figure 2 As shown, the particles are round and uniform in size, and the charge and discharge curves show good capacitance.

[0042] Example 2

[0043] The present embodiment is different from the embodiment 1 in that the molar ratio of the magnesium ion-doped lithium iron phosphate and the carbon-coated manganese dioxide in S1 is changed from "1.2:0.7" to "1.2:0.8".

[0044] The remaining raw materials and preparation process remain the same as in Example 1.

[0045] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0046] Example 3

[0047] The present embodiment is different from the embodiment 1 in that the "3 mL 0.5 mol / L MgSO4 solution" in S1 is changed to "4 mL 0.5 mol / L MgSO4 solution".

[0048] The remaining raw materials and preparation process remain the same as in Example 1.

[0049] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0050] Example 4

[0051] The present embodiment is different from the embodiment 1 in that "1.6 g KMnO4 and 2.6 g MnSO4·H2O" in S1 is changed to "1.8 g KMnO4 and 2.6 g MnSO4·H2O".

[0052] The remaining raw materials and preparation process remain the same as in Example 1.

[0053] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0054] Example 5

[0055] The present embodiment is different from the embodiment 1 in that "1.6 g KMnO4 and 2.6 g MnSO4·H2O" in S1 is changed to "1.6 g KMnO4 and 2.9 g MnSO4·H2O".

[0056] The remaining raw materials and preparation process remain the same as in Example 1.

[0057] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0058] Example 6

[0059] The present embodiment is different from the embodiment 1 in that the “15 mg manganese dioxide powder and 30 mg glucose” in S1 is changed to “15 mg manganese dioxide powder and 20 mg glucose”.

[0060] The remaining raw materials and preparation process remain the same as in Example 1.

[0061] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0062] Example 7

[0063] The present embodiment is different from the embodiment 1 in that the “15 mg manganese dioxide powder and 30 mg glucose” in S1 is changed to “15 mg manganese dioxide powder and 40 mg glucose”.

[0064] The remaining raw materials and preparation process remain the same as in Example 1.

[0065] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 As shown; the SEM image of lithium manganese iron phosphate material is as follows Figure 2 As shown, high carbon leads to increased residual carbon and uneven carbon layer, resulting in a smaller capacitance compared with the embodiment.

[0066] Example 8

[0067] Compared with Example 1, the present embodiment is different in that "a mixture of 9 g of magnesium ion-doped lithium manganese iron phosphate material, 1.5 g of lithium nitrate and 1.5 g of glucose" in S3 is changed to "a mixture of 9 g of magnesium ion-doped lithium manganese iron phosphate material, 1 g of lithium nitrate and 1 g of glucose".

[0068] The remaining raw materials and preparation process remain the same as in Example 1.

[0069] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0070] Example 9

[0071] The present embodiment is different from the embodiment 1 in that the “30 mg glucose” in S1 is changed to “67 mg PEG400”, and the “1.5 g glucose” in S3 is changed to “3.35 g PEG400”.

[0072] The remaining raw materials and preparation process remain the same as in Example 1.

[0073] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0074] Comparative Example 1

[0075] Compared with Example 1, this comparative example is different in that magnesium doping is not performed in S1. The specific implementation steps are as follows:

[0076] S1. Stir 130 mL PEG400, 35 mL 1 mol / L H3PO4 solution and 105 mL 1 mol / L LiOH solution evenly, adjust the pH value to stabilize at 12.0, add 40 mL 0.5 mol / LFeSO4 solution, stir for 5 min, react at 180 ° C for 12 h, wash, and dry to obtain lithium iron phosphate;

[0077] 1.6 g KMnO4 and 2.6 g MnSO4·H2O were added to 50 mL deionized water, and ultrasonically heated to 90°C until all the reagents were dissolved to obtain KMnO4 solution and MnSO4 solution; the KMnO4 solution was slowly and uniformly poured into the MnSO4 solution with continuous stirring, and reacted at 60°C for 1 h; vacuum filtered, washed, dried, and ground to obtain manganese dioxide powder; then 15 mg manganese dioxide powder and 30 mg glucose were added to 20 mL deionized water, stirred for 0.5 h, heated to 160°C, cooled to room temperature, washed, vacuum dried at 80°C for 12 h, and fully ground to obtain carbon-coated manganese dioxide.

[0078] Ball milling lithium iron phosphate and carbon-coated manganese dioxide in a molar ratio of 1.2:0.7 to obtain a mixed material;

[0079] The remaining raw materials and preparation process remain the same as in Example 1.

[0080] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0081] Comparative Example 2

[0082] Compared with Example 1, the difference between this comparative example and Example 1 is that the manganese dioxide in S1 is not carbon-coated. The specific implementation steps are as follows:

[0083] S1. Stir 130 mL PEG400, 35 mL 1 mol / L H3PO4 solution and 105 mL 1 mol / L LiOH solution, adjust the pH value to stabilize at 12.0, add 3 mL 0.5 mol / LMgSO4 solution and 40 mL 0.5 mol / LFeSO4 solution, stir for 5 min, react at 180 ° C for 12 h, wash, and dry to obtain magnesium ion-doped lithium iron phosphate;

[0084] 1.6 g KMnO4 and 2.6 g MnSO4·H2O were added to 50 mL deionized water, respectively, and ultrasonically heated to 90°C until all the reagents were dissolved to obtain KMnO4 solution and MnSO4 solution; the KMnO4 solution was slowly and uniformly poured into the MnSO4 solution with continuous stirring, and reacted at 60°C for 1 h; vacuum filtered, washed, dried, and ground to obtain manganese dioxide powder;

[0085] Ball milling is performed on lithium iron phosphate doped with magnesium ions and manganese dioxide in a molar ratio of 1.2:0.7 to obtain a mixed material;

[0086] The remaining raw materials and preparation process remain the same as in Example 1.

[0087] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0088] Comparative Example 3

[0089] Compared with Example 1, this comparative example differs in that no secondary calcination is performed, and the specific implementation steps are as follows:

[0090] S1. Stir 130 mL PEG400, 35 mL 1 mol / L H3PO4 solution and 105 mL 1 mol / L LiOH solution, adjust the pH value to stabilize at 12.0, add 3 mL 0.5 mol / LMgSO4 solution and 40 mL 0.5 mol / LFeSO4 solution, stir for 5 min, react at 180 ° C for 12 h, wash, and dry to obtain magnesium ion-doped lithium iron phosphate;

[0091] 1.6 g KMnO4 and 2.6 g MnSO4·H2O were added to 50 mL deionized water, and ultrasonically heated to 90°C until all the reagents were dissolved to obtain KMnO4 solution and MnSO4 solution; the KMnO4 solution was slowly and uniformly poured into the MnSO4 solution with continuous stirring, and reacted at 60°C for 1 h; vacuum filtered, washed, dried, and ground to obtain manganese dioxide powder; then 15 mg manganese dioxide powder and 30 mg glucose were added to 20 mL deionized water, stirred for 0.5 h, heated to 160°C, cooled to room temperature, washed, vacuum dried at 80°C for 12 h, and fully ground to obtain carbon-coated manganese dioxide.

[0092] Ball milling magnesium ion-doped lithium iron phosphate and carbon-coated manganese dioxide in a molar ratio of 1.2:0.7 to obtain a mixed material;

[0093] S2. 10 g of the mixed material, 1.5 g of lithium nitrate, 1.5 g of glucose and 60 mL of 1 mol / L phosphoric acid solution were mixed and sand-milled, dried, and calcined under inert gas protection to obtain lithium manganese iron phosphate material.

[0094] The remaining raw materials and preparation process remain the same as in Example 1.

[0095] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 shown.

[0096] Comparative Example 4

[0097] Compared with Example 1, the difference between this comparative example and Example 1 is that the manganese sources are directly mixed without carbon coating. The specific implementation steps are as follows:

[0098] S1. Stir 130 mL PEG400, 35 mL 1 mol / L H3PO4 solution and 105 mL 1 mol / L LiOH solution, adjust the pH value to stabilize at 12.0, add 3 mL 0.5 mol / LMgSO4 solution, 40 mL 0.5 mol / LFeSO4 solution and 80 mL 1 mol / LMnSO4 solution, stir for 5 min, react at 180 ° C for 12 h, wash, and dry to obtain magnesium ion-doped lithium manganese iron phosphate;

[0099] S2, mixing 10 g of magnesium ion-doped lithium manganese iron phosphate with 60 mL of 1 mol / L phosphoric acid solution, grinding, drying, and calcining under inert gas protection to obtain magnesium ion-doped lithium manganese iron phosphate material;

[0100] S3. 9 g of magnesium ion-doped lithium manganese iron phosphate material, 1.5 g of lithium nitrate and 1.5 g of glucose are mixed, sand-milled, dried, and calcined twice to obtain the lithium manganese iron phosphate material.

[0101] The 0.1C charge and discharge curve of the prepared lithium manganese iron phosphate material is as follows: Figure 1 As shown; the SEM image of lithium manganese iron phosphate material is as follows Figure 2 As shown, the absence of carbon in the Mn source leads to poor particle roundness and particle uniformity, which in turn leads to reduced capacity and cycle performance.

[0102] The lithium iron manganese phosphate materials obtained in the above Examples 1 to 9 and Comparative Examples 1 to 4 were used as positive electrode active materials for button batteries. The button batteries prepared in the Examples and Comparative Examples were subjected to capacity tests and cycle tests, and the test results are shown in Table 1 (where the first charge and discharge data are from Figure 1 ) as shown:

[0103] Table 1

[0104]

[0105] As can be seen from Table 1, compared with Example 1, the intrinsic conductivity of manganese iron phosphate is lower than that of lithium iron phosphate, and the increase of manganese content leads to a decrease in the specific capacity of the material; compared with Example 1, the content of doped magnesium ions is increased in Example 3, and excessive doping will block the diffusion of lithium ions, increase the charge transfer impedance and Mg 2+It does not provide capacity during the redox process, but reduces the capacitance; Examples 4 to 5 and Examples 8 to 9 only change the raw materials or raw material ratios made during the synthesis process, which has little effect on the capacitance of the material; Compared with Example 1, Example 6 reduces the amount of glucose added, which actually affects the content of carbon coated on the outer layer of manganese dioxide, resulting in reduced cycle performance of the material; and compared with Example 1, Example 7 has a tendency to reduce capacitance and cyclability due to excessive glucose content, because excessive carbon content will destroy the shell structure and form an irregular block structure, which is not conducive to the transmission of lithium ions.

[0106] Compared with Example 1, the results of Comparative Example 1 show that the material cyclability is reduced and the capacitance is reduced. This is because Mg 2+ The doping of Mg reduces the phase change of the material during the charge and discharge process, increases the transmission channel of Li+, and thus improves the capacity and cyclability; Combining Comparative Example 1, Example 1 and Example 3, excessive Mg 2+ Doping will reduce the performance of the material; in comparison with Example 2, Example 1 and Example 2, the manganese dioxide without carbon coating has Mn 4+ Transformed into Mn 3+ , Mn 3+ The carbon-coated manganese dioxide material forms a protective film on the surface of the MnO2 particles, which inhibits the growth of the grains, reduces the particle size, and shortens the MnO2 cycle. 4+ The deintercalation path in the solution is followed by the carbon in the MnO2 composite material forming a carbon layer with good conductivity on the surface of MnO2. The carbon layer protects the internal active material from being dissolved by the electrolyte and ensures that the structure of the active material is not destroyed. Comparative Example 2, Comparative Example 4 and Example 1 show that the manganese source used in the present invention is manganese dioxide coated with carbon, and the channels formed between the particles ensure that the electrolyte is in full contact with the active material, thereby improving the conductivity and charge and discharge efficiency of the material. The lithium manganese iron phosphate material obtained by direct mixing and drying is not sufficiently mixed and Mn 4+ Easily reacted to Mn 3+ , the recyclability is poor; compared with Example 1, it is concluded that the lithium manganese iron phosphate material obtained by the secondary calcination process has good energy storage performance and recyclability, thereby improving the quality of the product.

[0107] In summary, the present invention provides a method for preparing lithium manganese iron phosphate material based on the di-sintering process, which has high uniformity among the components of the material, high capacitance, good cyclability, and good commercial application prospects.

[0108] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0109] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing lithium manganese iron phosphate material based on a di-sintering process, characterized in that: The steps include: S1. Ball-milling magnesium ion-doped lithium iron phosphate and carbon-coated manganese dioxide to obtain a mixed material; S2, mixing the obtained mixed material with the phosphoric acid solution, sand-milling, drying, and calcining under the protection of an inert gas to obtain a magnesium ion-doped lithium manganese iron hydrogen phosphate material; S3, mixing the magnesium ion-doped lithium manganese iron phosphate material, lithium nitrate and a carbon source, sand-milling, drying, and secondary calcining to obtain the lithium manganese iron phosphate material.

2. The method for preparing lithium iron manganese phosphate material based on a di-sintering process according to claim 1, characterized in that: The molar ratio of the magnesium ion-doped lithium iron phosphate to the carbon-coated manganese dioxide is 1.1-1.2:0.7-0.

8.

3. The method for preparing lithium manganese iron phosphate material based on a di-sintering process according to claim 1, characterized in that: The mass ratio of the mixed material to the phosphoric acid solution is 1:6-8; the concentration of the phosphoric acid solution is 1 mol / L.

4. The method for preparing lithium iron manganese phosphate material based on a di-sintering process according to claim 1, characterized in that: The carbon source is one of glucose and PEG400; the mass ratio of the magnesium ion-doped lithium manganese iron hydrogen phosphate material, lithium nitrate and the carbon source is 9-10:1-1.5:1-1.

5.

5. The method for preparing lithium iron manganese phosphate material based on a di-sintering process according to claim 1, characterized in that: The magnesium ion-doped lithium iron phosphate is prepared by the following method: PEG400, 1 mol / L H3PO4 solution and 1 mol / L LiOH solution were stirred evenly, and when the pH value was adjusted to be stable at 11.5-12.0, 0.5 mol / L MgSO4 solution and 0.5 mol / L FeSO4 solution were added, stirred for 5-10 min, reacted at 180°C for 12-14 h, washed, and dried to obtain magnesium ion-doped lithium iron phosphate.

6. The method for preparing lithium iron manganese phosphate material based on a di-sintering process according to claim 5, characterized in that: The dosage ratio of the PEG400, H3PO4 solution, LiOH solution, MgSO4 solution and FeSO4 solution is 130-140 mL: 35-40 mL: 105-110 mL: 3-4 mL: 40-45 mL.

7. The method for preparing lithium iron manganese phosphate material based on a di-sintering process according to claim 1, characterized in that: The carbon-coated manganese dioxide is prepared by the following method: Add KMnO4 and MnSO4·H2O to deionized water respectively, and ultrasonically heat to 90°C until all the reagents are dissolved to obtain KMnO4 solution and MnSO4 solution; slowly and uniformly pour the KMnO4 solution into the MnSO4 solution while stirring continuously, and react at 55-60°C for 1-2h; vacuum filter, wash, dry, and grind to obtain manganese dioxide powder; Manganese dioxide powder and a carbon source are added to deionized water, stirred for 0.5 to 1 hour, heated to 150 to 160° C., cooled to room temperature, washed, vacuum dried at 75 to 80° C. for 12 to 14 hours, and fully ground to obtain carbon-coated manganese dioxide.

8. The method for preparing lithium iron manganese phosphate material based on a di-sintering process according to claim 7, characterized in that: The dosage ratio of KMnO4, MnSO4·H2O and deionized water is 1.6-1.8 g: 2.6-2.9 g: 50-60 mL.

9. The method for preparing lithium iron manganese phosphate material based on a di-sintering process according to claim 7, characterized in that: The carbon source is one of glucose and PEG400; the dosage ratio of the manganese dioxide powder, the carbon source and the deionized water is 15 mg: 20-40 mg: 20-30 mL.

Citation Information

Patent Citations

  • Method for preparing manganese phosphate lithium / carbon composite material

    CN102769131A